A love affair in the Dutch Reformed Church : a reflection - De Jongh, Erik (Stellenbosch Theological Journal, 2022)
As a community of silence, solitude and prayer, and a place of learning and formation the Andrew Murray Centre for Spirituality (AMCS) is a remarkable institution in the Dutch Reformed Church (DRC). In this article it will be studied from the perspective of spirituality, understood as an academic discipline. The leading question is how the AMCS can find its own way of learning as distinct from the learning in seminaries and local communities of the DRC. The chapter starts with an insider's perspective of the AMCS which provides the context for the research question. Based on Waaijman's distinction of three main forms of spirituality, the AMCS will be considered as a school of spirituality in the Reformed tradition. The connection between Andrew Murray and Bernard of Clairvaux will guide the further exploration of a truly authentic way of learning of the AMCS within the Reformed tradition.